Laminated body, optical device, imaging apparatus, and display apparatus
The laminate structure, featuring a layered anti-reflection coating with a first member containing fibers and a gap, and a second member with a lower refractive index, addresses the challenges of achieving high functionality and effective anti-reflection properties in optical instruments, resulting in enhanced light confinement and reduced reflectance.
Patent Information
- Application Number
- JP2023144269
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
Existing laminates and optical instruments face challenges in achieving high functionality and effective anti-reflection properties, particularly in suppressing stray light and maintaining low reflectance at various angles of incidence.
A laminate structure is proposed, where a first member with fibers and a binder, along with a gap, is stacked on a substrate, and a second member with a lower refractive index is added on top, creating a layered anti-reflection coating that enhances light confinement and reduces reflectance across different angles.
This laminate achieves superior anti-reflection functionality compared to prior art, providing low reflectance even at incident angles less than 45 degrees, while also maintaining high adhesion and porosity within the desired ranges.
Smart Images

Figure 2025037374000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, an optical instrument, an imaging device, and a display device. [Background technology]
[0002] A laminate is known in which a member having fibers and a binder is provided on a substrate. The laminate can be given functions such as hydrophilicity, antifouling, antibacterial properties, water resistance, and weather resistance according to the needs of the user. In addition, it is known that the laminate is used for optical purposes to suppress unnecessary reflected light and scattered light called stray light generated inside a housing. Patent Document 1 discloses an optical member having an antireflection film made of resin containing irregularly shaped fibers, which is intended to reduce the reflectance inside the housing. Patent Document 2 discloses an optical component having a coating film containing fine particles of multiple types of shapes. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-8843 A [Patent Document 2] JP 2011-64737 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the characteristics required of devices and equipment are increasing day by day, and better functionality is required. [Means for solving the problem]
[0005] An embodiment for solving the above problem is a laminate in which a first member and a second member are laminated in that order on a base material, the first member having fibers and a binder that binds the fibers, and the laminate having voids. Effect of the Invention
[0006] According to the above-described solution, for example, it is possible to provide a laminate having higher functionality than that of the prior art. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a schematic diagram showing a cross-sectional structure of a laminate according to an embodiment. [Diagram 2] 1A is a plan view of a laminated body having a shaped fiber, and FIG. 1B is a cross-sectional view of the shaped fiber. [Diagram 3] FIG. 11 is a schematic diagram showing a cross-sectional structure of a laminate according to a modified example. [Figure 4] Schematic diagrams showing deformation patterns of non-standard fibers (a) to (e). [Diagram 5] FIG. 1 is a schematic diagram showing an embodiment of an imaging device according to an embodiment. [Figure 6] FIG. 1 is a schematic diagram showing an example of a display device according to an embodiment. [Figure 7] 1 is a cross-sectional image of the laminate of Example 1. [Figure 8] FIG. 1A is a map of X-ray C Kα ray intensity in an EDS analysis of a cross section of the laminate of Example 1; FIG. 1B is a map of X-ray Si Kα ray intensity; and FIG. 1C is a graph showing the average value of the X-ray C Kα ray intensity and the Si Kα X-ray ray intensity in the Z direction, and the intensity ratio of the X-ray C Kα ray intensity and the Si Kα X-ray ray intensity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] The laminate of the present disclosure can be provided with functions such as hydrophilicity, antifouling properties, antibacterial properties, water resistance, and weather resistance according to the needs of users. It can also be used for optical applications. The following disclosure will focus on optical applications.
[0009] [Optical components] 1 is a schematic diagram showing a cross-sectional structure of a laminate according to an embodiment. An optical member 100, which is a laminate, has a base material 1 and an antireflection film 2 having a light reflecting surface 2A provided on the base material 1. The antireflection film 2 is formed by laminating a first member and a second member in this order.
[0010] (base material) The substrate 1 has a first surface 1A which is the front surface of the substrate, and a second surface 1B which is the back surface of the substrate opposite to the first surface 1A of the substrate. An antireflection film 2 is provided on the first surface 1A of the substrate in close contact with the first surface 1A of the substrate. A primer layer may be provided on the first surface 1A of the substrate to increase the adhesion to the antireflection film 2. The surface roughness of the first surface 1A of the substrate may be increased to increase the adhesion to the antireflection film 2.
[0011] The material of the substrate 1 is not particularly limited, and metals and resins can be used. Examples of metals include aluminum, aluminum alloys, titanium, titanium alloys, stainless steel, magnesium, and magnesium alloys. From the viewpoints of cost and durability, aluminum alloys and magnesium alloys are preferable. Examples of resins include polycarbonate resins, acrylic resins, ABS resins, and fluororesins.
[0012] (Anti-reflective film) The anti-reflection film 2 has a first member and a second member 23. The first member has fibers and a binder 21 that binds the fibers, and has voids 24. In this embodiment, the second member 23 has a lower refractive index than the first member. In this embodiment, the binder 21 is provided in close contact with the first surface 1A of the substrate 1. As described above, a primer layer may be provided between the substrate 1 and the binder 21.
[0013] <Resin> The binder 21 has a first surface 21A which is the surface of the binder. The binder 21 may have a plurality of voids 24. The binder 21 has a function of binding at least a part of the fibers. In addition, the fibers described later may be completely embedded in the binder 21.
[0014] The material constituting the binder 21 is not particularly limited, and inorganic materials and resin materials can be used. Examples of inorganic materials include silica binders. Examples of resin materials can be selected from acrylic resins, urethane resins, epoxy resins, and combinations thereof. In addition, either a solvent-soluble resin or a reaction-curing resin may be used. In order to increase the light absorption efficiency, the binder 21 is preferably dyed black with a black dyeing material. From the viewpoint of ease of dyeing black, the binder 21 is preferably a resin. The type of black dyeing material is not particularly limited, and for example, organic materials such as dyeing ink, metals such as nickel, cobalt, copper, and inorganic materials such as carbon black can be selected. Here, black refers to a color that has absorption in the entire range of light wavelengths from 380 nm to 780 nm. In addition, the binder 21 preferably has a blackness of 0.7 or more, which is indicated by the ratio of the maximum absorptance to the minimum absorptance in the light wavelength range from 380 nm to 780 nm.
[0015] The thickness of the binder 21 is not particularly limited, but is preferably in the range of 10 μm to 700 μm. When the thickness of the binder 21 is in this range, it is possible to achieve both good anti-reflection function and resistance to peeling. If the thickness of the binder 21 is thinner than 10 μm, there is a risk that the anti-reflection function will not be sufficiently obtained. On the other hand, if the thickness of the binder 21 exceeds 700 μm, there is a risk that the thickness will be easily uneven, and if the thickness unevenness becomes large, the binder 21 will be easily peeled off from the substrate 1. A more preferable thickness of the binder 21 is in the range of 20 μm to 500 μm.
[0016] <Textile> The fibers include those that are partly bound to the binder 21 and protrude from the first surface 21A, which is the surface of the binder 21, and those that are provided on the protruding fibers and do not contact the first surface 21A. The surfaces of the fibers 22 protruding from the first surface 21A are covered with the binder 21, and the surfaces of the fibers provided on the protruding fibers and not in contact with the first surface 21A are also covered with the binder 21. The angle between the length direction of the fibers (fiber axis direction) and the XY plane parallel to the substrate 1 is preferably less than 30 degrees. By arranging the fibers at the above-mentioned angle, the ratio of the voids 24 is set to a desired ratio, thereby enhancing the anti-reflection function. The ratio of the voids 24 will be described later.
[0017] Various types of fibers can be used depending on the optical performance required for the antireflection coating 2. For example, fibers whose cross section in a direction perpendicular to the fiber axis direction is a circle, an ellipse, or a convex polygon with all interior angles smaller than 180 degrees can be used, and irregularly shaped fibers 22 can also be used. Among these, it is preferable to use irregularly shaped fibers 22 from the viewpoint of further enhancing the antireflection function.
[0018] The irregular fiber 22 refers to a fiber whose cross-sectional shape in a direction perpendicular to the length direction (fiber axis direction) is other than a circle, an ellipse, and a convex polygon with all interior angles smaller than 180 degrees. In FIG. 1, a plurality of irregular fibers 22 protrude from the first surface 21A of the binder 21, and the angle between the length direction of the irregular fibers 22 and the XY plane parallel to the substrate 1 is less than 30 degrees, and the irregular fibers 22 are randomly stacked to surround a space, forming a plurality of voids 24. In order to prevent light rays (stray light) that deviate from the optical path that enters the anti-reflection film 2 from returning to the optical path, it is important to confine the light by reflecting it multiple times within the anti-reflection film 2. Although the irregular shape of the fiber alone has the effect of confining light, the presence of a plurality of voids 24 can further increase the effect. In particular, even if light rays with a high angle of incidence exceeding 80 degrees enter the first surface 21A of the binder, they are less likely to return to the optical path by hitting the plurality of irregular fibers 22.
[0019] The content of the irregular fibers 22 in the first component is preferably 33 parts by mass or more and 67 parts by mass or less per 100 parts by mass. 33 parts by mass or more is preferable in order to facilitate protrusion from the binder 21, and 67 parts by mass is preferable in terms of expanding the diversity of the manufacturing method described below. In addition, the content of fibers other than the irregular fibers in the first component is preferably in the range of 40 parts by mass or more and 80 parts by mass or less per 100 parts by mass of the antireflection film.
[0020] FIG. 2 is a schematic diagram of a non-circular fiber that can be used in the laminate of this embodiment. FIG. 2(a) is a plan view, and FIG. 2(b) is a cross-sectional view of the non-circular fiber 22 cut along line IIIB-IIIB in FIG. 2(a). The non-circular fiber 22 has a core 221 and a plurality of legs 222 extending from the core 221. The core 221 is the part drawn by a dotted line in FIG. 2(b), and has a circular cross section. However, the core 221 does not necessarily have to be circular, and may be angular. The thickness T221 of the core (the length of the cross section in the direction perpendicular to the length direction of the non-circular fiber) represents the diameter of the circle when the core is circular. In addition, when the core is polygonal, it represents the diameter of the inscribed circle of the polygon, and when the core is elliptical, it represents the diameter of the major radius side. The core 221 may have a hole 223.
[0021] The legs 222 extend from the core 221 and are made of the same material as the core 221. In FIG. 2(b), the number of legs 222 is eight, but the number of legs is not limited to eight. Of the parts of the irregular fiber 22, the parts protruding from the first surface 21A of the binder are preferably the legs 222. This is because the multiple legs 222 protruding from the first surface 21A can diffuse the light beam incident between the two legs and make it difficult for the light beam to return to the light path. In the irregular fiber, in order to diffuse the light beam between the legs more efficiently, it is preferable that the number of legs is three or more and eight or less. For example, Octa (registered trademark) manufactured by Teijin Frontier Co., Ltd. is a commercially available irregular fiber having eight legs. It is difficult to manufacture a fiber having nine or more legs.
[0022] The length L222 of the legs is preferably in the range of 5 μm or more and 20 μm or less. When the length L222 of the legs is in this range, the effect of reducing the reflectance is large. When the length L222 of the legs is smaller than 5 μm, the length of the legs 222 protruding from the first surface 21A of the binder is short, and the reflection of light between the legs is not sufficient, and the effect of reducing the reflectance may be insufficient. On the other hand, when the length L222 of the legs is larger than 20 μm, the legs may tilt or fall, and the light rays may not penetrate sufficiently between the legs, and the effect of reducing the reflectance may be insufficient. More preferably, the length is in the range of 5 μm or more and 12.5 μm or less.
[0023] The leg thickness T222 is preferably in the range of 2 μm or more and 6 μm or less. When the leg thickness T222 is in this range, the reflectance reduction effect is large. When the leg thickness T222 is thinner than 2 μm, the legs may tilt or fall, and light may not be able to penetrate sufficiently between the multiple legs, resulting in an insufficient reflectance reduction effect. On the other hand, when the leg thickness T222 is thicker than 6 μm, the interval between the multiple legs becomes small, and light may not be reflected sufficiently between the multiple legs, resulting in an insufficient reflectance reduction effect.
[0024] The length L22 of the irregular fiber is preferably in the range of 0.2 mm or more and 1.0 mm or less. When the length L22 of the irregular fiber is in this range, the anti-reflection function is enhanced. When the length L22 of the irregular fiber is shorter than 0.2 mm, the proportion of the cut surface of the irregular fiber that does not have the anti-reflection function protruding from the first surface 21A of the binder increases, and the anti-reflection function may be insufficient. On the other hand, when the length L22 of the irregular fiber is longer than 1.0 mm, it may be difficult to make the leg part 222 of the irregular fiber protrude from the first surface 21A of the binder 21 when the anti-reflection film is formed. The length of the irregular fiber can be cut to a desired length by a cutter.
[0025] The aspect ratio, which is the ratio of the length L22 to the thickness T22 of the irregular fiber (L22 / T22), is preferably in the range of 4 to 100. When the aspect ratio is in this range, when an antireflection film is formed, the angle between the length direction of the multiple irregular fibers 22 and the XY plane parallel to the first surface 1A of the substrate 1 is easily made less than 30 degrees. However, when the aspect ratio is smaller than 4 and approaches an isotropic shape, the angle between the substrate 1 and the XY plane parallel to the first surface 1A is easily made to exceed 30 degrees, and the probability that the incident light will hit the cut surface of the irregular fiber with low antireflection performance increases, which may result in insufficient antireflection performance.
[0026] The material of the fiber is not particularly limited, and can be selected from, for example, glass fiber, metal fiber, polyester, nylon, acrylic, polypropylene, rayon, polyethylene, polyurethane, cotton, hemp, knitted wool, and combinations thereof. In order to improve the performance of the anti-reflection film, the irregularly shaped fiber may be processed, light-resistant, softened, or fade-resistant.
[0027] In order to increase the light absorption efficiency, the irregular fiber 22 is preferably dyed black with a black dyeing material. From the viewpoint of ease of dyeing black, it is preferable to select from polyester, nylon, acrylic, polypropylene, rayon, polyethylene, polyurethane, cotton, linen, knitted wool, and combinations thereof. The type of black dyeing material is not particularly limited, and for example, organic materials such as dye ink, metals such as nickel, cobalt, copper, and inorganic materials such as carbon black can be selected.
[0028] <Second component> The second member 23 is preferably a member having a lower refractive index than the first member and a refractive index closer to that of air than the first member. If the refractive index of the second member 23 is lower than that of the first member, the antireflection film 2 has a lower reflectance at a low incidence angle. The refractive index is a refractive index in the wavelength range of 500 nm to 600 nm. The refractive index of the second member 23 is preferably 1.4 or less, and more preferably 1.35 or less. In this embodiment, the second member is provided on the surface of the laminate opposite to the substrate 1. In the embodiment of FIG. 1, the second member 23 is provided more on the upper layer side of the antireflection film 2 so as not to reduce the amount of the voids 24. When the total thickness of the first member and the second member is T, the region up to a thickness T / 2 on the side farther from the substrate 1 is the upper layer, and the region up to a thickness T / 2 on the side closer to the substrate 1 is the lower layer. At this time, it is preferable that the second member 23 is present more in the upper layer than in the lower layer. The fact that the second member 23 is less present in the lower layer of the anti-reflection film 2 means that the number of voids in the first member or its structure is not changed by the second member 23. Therefore, the function of lowering the reflectance at a high incidence angle, which can be expressed by a structure such as that disclosed in JP 2020-8843 A, can also be guaranteed. In this embodiment, since there is a large amount of the second member 23 in the upper layer of the anti-reflection film 2, the refractive index change at the interface between the anti-reflection film 2 and the air layer becomes more gradual, and the reflectance at a low incidence angle (for example, an incidence angle of 45 degrees or less) can be further reduced. In addition, although the fibers present in the upper layer of the anti-reflection film 2 are bound by the binder 21, there are many fibers that are not in contact with the first surface 21A, which is the surface of the binder 21. In other words, there are many fibers that are covered with the binder 21 but have further fibers placed on top of the fibers. Such fibers have a weaker binding force than those contained in the first surface 21A. However, since a large amount of the second member 23 is present in the upper layer of the antireflection film 2, the adhesive strength of the fibers can be reinforced, and therefore peeling of the fibers that are not in contact with the first surface 21A, which is the surface of the resin, can be prevented. Therefore, when the fibers are made of the irregular fibers 22, it is possible to increase the content of the irregular fibers 22 and stack more irregular fibers 22 than in the antireflection film disclosed in JP2020-8843A, thereby enabling a further reduction in reflectance.
[0029] The thickness of the second member 23 is preferably in the range of 100 nm to 1200 nm. More preferably, the thickness of the second member 23 is in the range of 200 nm to 800 nm. If the thickness is 200 nm or more, the effect of reducing the reflectance at a low angle of incidence in optical applications is more excellent. If the thickness is 800 nm or less, the effect of reducing the reflectance at high and low angles of incidence is more excellent.
[0030] The second member 23 is preferably transparent. In the present disclosure, the term "transparent" refers to a transmittance of 10% or more for light having a wavelength in the range of 400 nm or more and 780 nm or less.
[0031] The material of the second member 23 is not particularly limited, but it is preferable that the material can form a film by wrapping around the depressions (positions between the legs) of the irregular fibers 22 and the overlapping parts of the irregular fibers 22, and furthermore, it is preferable that the material can reinforce the binding force between the irregular fibers 22. From this viewpoint, a material using a resin material or inorganic particles can be used, but it is preferable to use inorganic particles and a binder. As a material using inorganic particles, silica or magnesium fluoride can be used, but silicon oxide particles (hereinafter, silica particles) that have a high affinity with the silica binder used to bind the inorganic particles and can form a strong bond are more preferable. As the resin, a fluororesin can be used. Since the fluororesin has excellent antifouling properties, it is possible to achieve both optical properties and antifouling properties.
[0032] The shape of the silica particles is not particularly limited, and examples thereof include spherical, cocoon-shaped, bale-shaped, disc-shaped, rod-shaped, needle-shaped, angular, and chain-shaped shapes. In order to form more voids and lower the refractive index, shapes other than spherical, such as hollow particles and chain-shaped particles, are preferable. As the shape of the silica particles, hollow particles having a hollow part inside a spherical shell and chain-shaped particles which are hydrophilic particle links are preferable. The hollow particles can lower the refractive index of the second member 23 by forming the gas (refractive index 1.0) contained in the hollow part into the void part in the anti-reflection film 2, which will be described later. The hollow part may be either single-hole or multi-hole, and can be appropriately selected. As a method for producing hollow particles, for example, they can be produced by the method described in JP-A-2001-233611 and JP-A-2008-139581.
[0033] Chain-like silica particles are SiO 2The particles are mainly composed of, and among the elements excluding oxygen, Si is preferably 80 atomic % or more, and more preferably 90 atomic % or more. If Si is less than 80 atomic %, the number of silanol (Si-OH) groups on the particle surface that react with the silica binder decreases, which may reduce the binding force. The average particle diameter of the chain particles is preferably in the range of 10 nm to 50 nm in the short axis and 60 nm to 200 nm in the long axis. The short axis roughly corresponds to the diameter of the solid particles. If the short axis is smaller than 10 nm or the long axis is smaller than 60 nm, the gap between the chain particles becomes small, so the refractive index may not be sufficiently low. Also, if the short axis exceeds 50 nm or the long axis exceeds 100 nm, the size of the gap between the chain particles becomes large, so the binding force between the particles becomes weak, and as a result, the binding force of the fibers in the upper layer of the anti-reflection film 2 may become insufficient. The average particle diameter of the particles when the solid particles are connected in a chain shape is the average Feret diameter. The average Feret's diameter can be measured by image processing of an image observed by a transmission electron microscope. As an image processing method, a commercially available image processing such as Image Pro PLUS (manufactured by Media Cybernetics) can be used. In a predetermined image area, the contrast is appropriately adjusted if necessary, the average Feret's diameter of each particle is measured by particle measurement, and the average value is calculated. Examples of commercially available chain particles include Snowtex-OUP, Snowtex-UP (registered trademark), IPA-ST-UP (registered trademark), and MEK-ST-UP (registered trademark) manufactured by Nissan Chemical Industries, Ltd. These silica sols have an irregularly bent shape.
[0034] The silica binder can be appropriately selected depending on the film binding strength and environmental reliability, but it is preferable to use a silica binder because it has a high affinity with silica particles and improves the porous film binding strength. Among silica binders, it is more preferable to use a silicate hydrolysis condensate. The weight average molecular weight of the silica binder is preferably 500 to 3000 in polystyrene equivalent. If the weight average molecular weight is less than 500, cracks are likely to occur after curing, and the stability as a paint is reduced. In addition, if the weight average molecular weight exceeds 3000, the viscosity increases, so that the voids inside the binder tend to become uneven, and large voids are generated, which may reduce the binding strength between particles. The content of the binder is preferably in the range of 2% by mass to 30% by mass, and more preferably in the range of 3% by mass to 20% by mass, relative to the low refractive index portion.
[0035] <Void> The porosity, which indicates the ratio of the voids 24 in the anti-reflection film 2 made of the first member and the second member, is preferably in the range of 50% to 90%. A method for measuring the porosity will be described later. When the porosity satisfies the above range, the function of lowering the reflectance of the laminate at a high incidence angle can be more easily ensured. The voids 24 may be present in the binder 21 and the second member 23, but are preferably formed in a space surrounded by fibers from the viewpoint of easy manufacturing. In addition, the maximum circle equivalent diameter of the voids 24 formed in the space surrounded by the fibers is preferably in the range of 1 μm to 200 μm. In this range, the adhesion of the fibers to the second member 23 can be made sufficient. In addition, the maximum circle equivalent diameter of the voids 24 formed in the second member 23 is preferably in the range of 5 nm to 100 nm. That is, the voids formed in the second member 23 are preferably smaller than the voids of the first member formed in the space surrounded by the fibers 22.
[0036] As described above, the laminate of the present disclosure is a laminate in which a first member and a second member are laminated in order on a substrate, the first member has fibers and a binder that binds the fibers, and has voids. Furthermore, if the second member has a lower refractive index than the first member, it is possible to achieve both the light confinement effect at a high incidence angle of more than 80 degrees due to the voids and the reflection function at low incidence due to the second member with a low refractive index, so that a laminate with better anti-reflection function than the conventional technology can be provided. In particular, it is possible to provide an optical member that can achieve low reflectance even at a low incidence angle of 45 degrees or less.
[0037] (Modification) 3 is a schematic diagram showing a cross-sectional structure of a modified laminate 100B. The laminate 100B differs from the laminate 100 in that the fibers are not protruding from the surface of the binder 21 but are entirely embedded therein. This configuration reduces the rough feeling felt by the user and enhances the design. Instead, the voids 24 are formed in the binder 21. A resin material may be used as the binder to form a porous structure (porous body), or the voids 24 may be formed by incorporating hollow particles into the resin material.
[0038] The irregular fiber 22 is not limited to the fiber having eight legs used in the above-described embodiment. FIG. 4 is a schematic diagram showing a modified example of the irregular fiber 22.
[0039] FIG. 4(a) shows a Y-shaped irregular fiber 22A in which three legs 222A extend from a core 221A. FIG. 4(b) shows an irregular fiber 22B in which eight legs 222B with pointed ends extend from a core 221B. FIG. 4(c) shows an irregular fiber 22C in which three legs 222C arranged at non-equidistant intervals extend from a core 221C. FIG. 4(d) shows an irregular fiber 22D in which four legs 222D of non-uniform size extend from a rectangular core 221D in a plan view. FIG. 4(e) shows a cross section of the irregular fiber 22D different from that shown in FIG. 4(d), and thus the cross sections of the irregular fiber in the direction perpendicular to the length direction do not need to be the same. An example of a fiber having such a shape is a crimped fiber in which each fiber is shrunk and wound. Commercially available crimped fibers include Calcuro (registered trademark) manufactured by Teijin Frontier Co., Ltd. These modified examples also have the same anti-reflection function as the above-mentioned embodiment.
[0040] In addition, the laminate of the present disclosure can be provided with functions such as hydrophilicity, antifouling, antibacterial properties, water resistance, and weather resistance according to the needs of the user. Therefore, the second member 23 may be a functional member having functions such as hydrophilicity, antifouling, antibacterial properties, water resistance, and weather resistance, instead of a member having a low refractive index. In addition, a functional film having functions such as hydrophilicity, antifouling, antibacterial properties, water resistance, and weather resistance may be further provided on the second member 23.
[0041] [Method of manufacturing laminate] The method for producing the laminate is not particularly limited, but an example will be described below.
[0042] For example, a resin material that is a precursor of the binder 21, paint A containing fibers and the like, and paint B containing silica particles and a silica binder are prepared. First, paint A is applied to the substrate 1, and then paint B is applied, thereby manufacturing the laminate 100.
[0043] <Paint A> The paint A contains fibers, a resin material that is a precursor of the binder 21, and an organic solvent. By applying and curing the paint A, a first member having the binder 21, the irregular fibers 22, and voids 24 can be formed. Below, an example using the irregular fibers 22, which are suitable as fibers, will be described.
[0044] The content of the irregular fibers contained in the paint A is preferably in the range of 50 parts by mass to 200 parts by mass with respect to 100 parts by mass of the paint solids before mixing the irregular fibers. Here, the paint solids refers to all solid components contained in the paint A, including not only the precursor of the binder 21 but also additives. If the content of the irregular fibers is less than 30 parts by mass, there is a risk that the anti-reflection function is not sufficiently obtained. On the other hand, if it is more than 200 parts by mass, there is a risk that the tip of the spray nozzle is easily clogged when applying the paint with a spray gun. Even if an anti-reflection film can be formed, since the amount of paint solids such as resin is small, the bond between the resin and the irregular fibers is insufficient, and the irregular fibers may easily fall off. In order to make it easier to protrude from the resin, the range is preferably 50 parts by mass to 200 parts by mass. In other words, the content of the irregular fibers is 33 parts by mass to 67 parts by mass with respect to 100 parts by mass of the paint solids, if the irregular fibers are also considered as part of the solids.
[0045] The resin material contained in the paint A constitutes the binder 21 after the paint is dried. The type of the resin material is not particularly limited, and can be selected from, for example, acrylic resin, urethane resin, epoxy resin, and combinations thereof. In addition, either a solvent-soluble resin or a reaction-curing resin may be used.
[0046] The type of organic solvent contained in the paint A is not particularly limited, and examples thereof include water, thinner, ethanol, isopropyl alcohol, n-butyl alcohol, ethyl acetate, propyl acetate, isobutyl acetate, and butyl acetate. Other examples include methyl ethyl ketone, methyl isobutyl ketone, propylene glycol monomethyl ether, toluene, xylene, acetone, cellosolves, glycol ethers, and ethers. These solvents may be used alone or in combination.
[0047] The coating method of the paint A is not particularly limited, and any ordinary coating method such as brush coating, doctor blade coating, coating using a bar coater, spray coating, and spin coating can be adopted. Among them, spray coating is preferred from the viewpoint of excellent conformability to the substrate shape. The method of curing the paint A is also not particularly limited, and it may be dried at room temperature (for example, 23°C ± 2°C), curing may be accelerated by heat, or ultraviolet light may be applied. The organic solvent is preferably 5 parts by mass or more and 80 parts by mass or less with respect to 100 parts by mass of the paint A. If the content of the organic solvent is less than 5 parts by mass, it may be difficult to make the first member into a thin layer. In addition, when applying with a spray gun, the discharge part of the spray gun may be clogged, narrowing the options for the manufacturing method. On the other hand, if the content of the organic solvent exceeds 80 parts by mass, the adhesion between the substrate 1 and the first member may be deteriorated. In addition, sagging may occur when applying with a spray gun. The viscosity of the paint A is preferably 10 mPa·s or more and 200 mPa·s or less. If the viscosity of paint A is less than 10 mPa·s, the adhesion between the substrate 1 and the first member may deteriorate, while if it is greater than 200 mPa·s, it may become difficult to form the first member into a thin layer.
[0048] In the paint A, in order to improve the dispersibility of the irregular fibers 22, a coating treatment can be applied to the surface of the irregular fibers 22. For the coating treatment, surfactants, inorganic salts, and various resins can be used. As an example of the surface treatment, the surface of the irregular fibers cut to a desired length is treated with a tannin compound, tartar emetic, etc., to generate the tannin compound, etc. on the fiber surface. In this way, the water retention of the tannin compound, etc. is utilized to maintain good electrical conductivity of the flock surface. Alternatively, inorganic salts, inorganic silicon compounds, surfactants, and mixtures thereof are attached to the surface of the irregular fibers. Examples of the tannin compound include natural tannin and synthetic tannin. Examples of the inorganic salt include sodium chloride (NaCl), barium chloride (BaCl), etc. 2 ), magnesium chloride (MgCl 2 ) and magnesium sulfate (MgSO 4 ), sodium silicate (Na 2 SiO 3 ), Sodium Carbonate (Na 2 CO 3 ), Sodium sulfate (Na 2 SO 4 ) can be mentioned. Examples of inorganic silicon compounds include colloidal silica. Examples of surfactants include anionic surfactants, nonionic surfactants, amphoteric surfactants, and cationic surfactants.
[0049] The method for producing the paint A is not particularly limited as long as the irregular fibers 22 can be dispersed in the paint A. The irregular fibers 22 may be put into a container containing an organic solvent, or the organic solvent may be put into a container containing the irregular fibers 22. Examples of the dispersion method include a bead mill, a ball mill, a jet mill, a three-roller, a planetary rotation device, a mixer, and an ultrasonic disperser.
[0050] <Paint B> The paint B contains silica particles and a silica binder which is an inorganic particle binder. By applying and curing the paint B, the second member 23 and the gap 24 can be formed.
[0051] The concentration of silica particles may be selected as appropriate depending on the film thickness required for the second member 23, and is preferably 3% by mass or more and 20% by mass or less in terms of oxide. If it is 3% by mass or less, multiple coatings are required to obtain the required film thickness, and if it is 20% by mass or more, the particles are likely to aggregate. It is preferable that the silica particles are chain-shaped particles.
[0052] The silica binder is preferably a material that forms siloxane bonds between chain particles to bond the particles together. The binder may be used by mixing a solution containing components necessary for forming a binder made of silane alkoxy hydrolysis condensate with a solution in which chain particles are dispersed in a solvent. Alternatively, a solution in which solid particles are linked in a chain shape and dispersed in a solvent may be applied, the particles may be aligned, and then a solution containing components necessary for forming the binder may be applied.
[0053] A solution containing a silane alkoxy hydrolysis condensate can be used as a solution containing components necessary for forming an inorganic particle binder. The solution containing a silane alkoxy hydrolysis condensate can be prepared by stirring and reacting an alkoxysilane with water to hydrolyze the alkoxysilane to produce a silane alkoxy hydrolysis condensate.
[0054] Since alkoxysilane, the precursor of silane alkoxy hydrolysis condensation product, is not compatible with water, when alkoxysilane is mixed with water, the mixture is in a two-layered state at the beginning of the reaction. As the reaction progresses, the alkoxide becomes silanol, and the hydrophilic group increases, so that the hydrolyzate of alkoxysilane dissolves in the water layer, eliminating the two-layered state and resulting in a uniform mixture.
[0055] If the concentration of the hydrolyzate of alkoxysilane in the water layer becomes too high, the reaction with water will proceed rapidly, causing gelation or an increase in viscosity. Therefore, it is preferable to add a water-soluble solvent in an amount of 10% by mass or more relative to the raw alkoxysilane. The water-soluble solvent referred to here refers to a solvent in which the solubility of water in the solvent at 23°C is 80% by mass or more. The water-soluble solvent is preferably cellosolve or glycol ether. Examples of the water-soluble solvent include 2-methoxyethanol, 2-ethoxyethanol, 2-isopropoxyethanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol.
[0056] As the inorganic particle binder to be used by mixing with the chain particles, the liquid temperature of the solution in which the silane alkoxy hydrolysis condensate produced by hydrolyzing the alkoxysilane and water are uniformly mixed is preferably higher than 5°C and lower than 30°C. If the silane alkoxy hydrolysis condensate is below 5°C, it takes too long to hydrolyze, resulting in poor productivity. Also, if the temperature is above 30°C, the condensation reaction proceeds and the silane alkoxy hydrolysis condensate grows too much, which increases scattering due to the silane alkoxy hydrolysis condensate and scattering due to the increase in the size of the voids formed between the chain particles, which is not preferable.
[0057] The progress of hydrolysis and condensation reaction of the silane alkoxy hydrolysis condensate can be evaluated by the average particle size. The silane alkoxy hydrolysis condensate preferably has an average particle size of 8 nm to 30 nm measured by dynamic light scattering of a solution containing components necessary for forming an inorganic particle binder. More preferably, the silane alkoxy hydrolysis condensate has an average particle size of 8 nm to 15 nm.
[0058] As the alkoxysilane, a trifunctional silane modified with a methyl group, such as methyltriethoxysilane or methyltrimethoxysilane, a tetrafunctional silane, such as tetraethoxysilane, or a mixture of the above trifunctional silane and tetrafunctional silane may be used. Increasing the number of silanol groups increases the probability of forming a siloxane bond at the contact point of the particles, thereby increasing the strength of the anti-reflective coating, so it is particularly preferable to use a tetrafunctional silane.
[0059] The concentration of the components necessary for forming the inorganic particle binder can be appropriately selected depending on the concentration of the chain particles, but it is preferable that the concentration is 0.2 mass% or more and less than 1.5 mass%, because it provides a suitable strength for the second member. Furthermore, it is preferable that the concentration is 0.2 mass% or more and less than 1.0 mass%. If the concentration is less than 0.2 mass%, it is insufficient to bond the particles together, and the strength of the film is weakened. On the other hand, if the concentration is high, such as 1.5 mass% or more, the components necessary for forming the inorganic particle binder in the particle film become excessive, filling the voids, and the refractive index increases, thereby reducing the anti-reflection effect.
[0060] As the dispersion medium used in the dispersion liquid, it is possible to appropriately select one that has a good affinity with silica particles. If the dispersion medium has low affinity, aggregation is observed. Furthermore, if the affinity between the solvent contained in the solution containing the components necessary to form the inorganic particle binder and the components necessary to form the inorganic particle binder is low, the components necessary to form the inorganic particle binder are not compatible. Furthermore, even if the components are dispersed and compatible as a paint, they will aggregate or separate during film formation, resulting in a whitening phenomenon. As a suitable dispersion medium or solvent, it is preferable to use one with a boiling point of 100°C or more and 200°C or less. The solvent needs to be selected depending on the hydrophilicity and hydrophobicity of the hollow particle surface. When the hollow particles are hydrophobized by treating them with a silane coupling agent, the solvent contained in the solution containing the components necessary to form the binder is preferably a hydrophilic solvent. It is preferable to use a trifunctional silane modified with a methyl group, such as methyltriethoxysilane or methyltrimethoxysilane, as the precursor of the hollow particles. It is preferable that the solution containing the components necessary to form the binder contains a solvent in which the solubility of water in the solvent is 10 mass% or less in addition to a hydrophilic solvent as a solvent. The solution containing the components necessary for forming the inorganic particle binder preferably contains 70% by mass or more of a solvent in which the solubility of water in the solvent is 10% by mass or less. Examples of the solvent in which the solubility of water in the solvent is 10% by mass or less include 4-methyl-2-pentanol, 2-pentanol, 2-methyl-1-butanol, 3-methyl-1-butanol, and 2-ethyl-1-butanol. The dispersion liquid contains one or more of these solvents.
[0061] The concentration of the components necessary to form the binder in the solution containing the components necessary to form the inorganic particle binder may be determined so as to provide a desired content in the formed particle film, and the concentration can be appropriately selected depending on the solvent and film formation conditions.
[0062] The second member 23, which is formed in greater quantity in the upper layer of the anti-reflection coating 2, is formed by coating with paint B. The second member 23 has multiple chain-like particles piled up on its surface, and the chain-like particles are bound together with a binder. The air (refractive index 1.0) contained in the nano-sized voids makes the refractive index of the second member 23 lower than the refractive index of the particles themselves, which are solid particles connected in a chain shape.
[0063] The method of coating the second member 23 is not particularly limited, and any ordinary coating method can be used, such as brush coating, coating using a doctor blade or bar coater, spray coating, or spin coating. In particular, spray coating is preferable to reduce the reflectance at a low incidence angle. In spray coating, the concentration of droplets increases as the solvent evaporates in the air as the droplets are ejected from the nozzle. At this time, the viscosity and surface tension of the droplets increase, so they do not penetrate much into the lower layer, which is the first member side of the anti-reflection film 2, and the second member can be formed on the upper layer including the light incidence surface.
[0064] [Optical instruments and imaging devices] 5 is a schematic diagram showing an embodiment of the configuration of a single-lens reflex digital camera 600, which is an example of an imaging device, including a lens barrel, which is an example of a preferred embodiment of the imaging device of the present disclosure. In Fig. 5, a camera body 602 and a lens barrel 601, which is an optical device, are coupled together, and the lens barrel 601 is a so-called interchangeable lens that is detachable from the camera body 602.
[0065] Light from a subject passes through an optical system consisting of multiple lenses 603, 605, which are an example of components arranged on the optical axis of the photographing optical system inside the housing of the lens barrel 601, and is received by an image sensor, thereby photographing the subject. Here, the lens 605 is supported by an inner tube 604, and is supported movably relative to the outer tube of the lens barrel 601 for focusing and zooming. The inner tube 604 is a support body that supports the lens 605.
[0066] During an observation period before shooting, light from a subject is reflected by a main mirror 607, which is an example of a component in a housing 621 of the camera body, and after passing through a prism 611, a shooting image is projected to the photographer through a viewfinder lens 612. The main mirror 607 is, for example, a half mirror, and the light passing through the main mirror is reflected by a sub-mirror 608 in the direction of an AF (autofocus) unit 613, and this reflected light is used, for example, for distance measurement. The main mirror 607 is attached and supported by a main mirror holder 640 by adhesive or the like. During shooting, the main mirror 607 and the sub-mirror 608 are moved out of the optical path via a driving mechanism (not shown), a shutter 609 is opened, and a shooting light image incident from the lens barrel 601 is formed on an image sensor 610. The aperture 606 is configured so that the brightness and focal depth during shooting can be changed by changing the opening area.
[0067] To apply the laminate 100 of the present disclosure to a lens barrel, the housing 620 is configured in the same manner as the substrate 1, and an anti-reflection film 630 having the same configuration as the anti-reflection film 2 is provided on the inner wall surface 620A of the housing. Alternatively, the inner tube 604 is configured in the same manner as the substrate 1, and an anti-reflection film 630 having the same configuration as the anti-reflection film 2 is provided on the first surface 604A of the support, which is the surface on the side supporting the lens of the inner tube. By adopting such a configuration, light rays that are not imaged and do not contribute to the formation of the subject image among the light rays incident on the optical device are unlikely to return to the optical path by hitting the irregular fiber. As a result, the amount of stray light that reaches the image sensor 610 is reduced. According to the imaging device of the present disclosure, the amount of stray light that reaches the image sensor is reduced, so that an imaging device with excellent quality of captured images can be provided in which flare and ghosts are unlikely to occur.
[0068] Although the imaging device has been described using a single-lens reflex digital camera as an example, the present disclosure is not limited to this, and the imaging device may also be a smartphone or a compact digital camera.
[0069] <Display device> FIG. 6 is a schematic diagram showing one embodiment of the configuration of a head-up display 300, which is an example of a preferred embodiment of the display device of the present disclosure.
[0070] The head-up display 300 is installed in a vehicle such as an automobile, projects image light onto a windshield 8, which is an example of a display unit, and displays a virtual image IM that can be viewed by a viewer, that is, a driver having eyes 9. The head-up display 300 has a housing 3, an image generating unit 4, and reflecting mirrors 51 and 52. The head-up display 300 is installed, for example, in a dashboard in front of a steering wheel H.
[0071] The image generating unit 4 is provided inside the housing 3. The image generating unit 4 has a light source 42 and a display panel 41. The light source 42 is a device that emits light, and is, for example, a plurality of LEDs. The display panel 41 is a device that modulates the light emitted from the light source 42 to generate image light, and is, for example, a self-luminous display such as a transmissive liquid crystal display or an organic EL display.
[0072] The reflecting mirrors 51 and 52 are provided inside the housing 3. The reflecting mirrors 51 and 52 each have a reflecting surface 51A, 52A, and reflect the image light generated by the image generating unit 4 at each reflecting surface. The generated image light may pass through an optical path via a condenser lens 53 or the like as necessary before being reflected by the reflecting surface 51A. The reflecting mirror 52 has a driving mechanism 521 including a motor, gears, etc., and the driving mechanism 521 is driven by a control device (not shown) to adjust the angle of the reflecting surface 52A. The reflecting mirrors 51 and 52 are each a concave mirror. The reflecting mirrors 51 and 52 each have a metal film such as aluminum formed on the surface of a base material having a free-form surface shape made of resin. The metal film can be formed by, for example, deposition. The image light reflected by the reflecting mirror 52 is magnified and projected toward the windshield 8 located outside the housing 3 via the transmitting plate 7. The transmitting plate 7 is, for example, an acrylic plate.
[0073] To apply the laminate 100 of the present disclosure to a display device, the housing 3 has the same configuration as the substrate 1, and an antireflection film 10 having the same configuration as the antireflection film 2 is provided on the inner wall surface 3A of the housing. By adopting such a configuration, light rays generated when the backlight of the head-up display is turned on or when external light is incident, and light rays that do not contribute to the formation of the image light reflected inside the housing, are unlikely to return to the optical path by hitting the irregular fiber. As a result, the amount of stray light reaching the display area 81 of the windshield 8 is reduced. According to the display device of the present disclosure, since the amount of stray light reaching the windshield 8 is reduced, a display device with excellent quality of the image (virtual image) generated from the image light can be provided.
[0074] In the embodiment of the display device of the present disclosure, the head-up display is installed in an automobile, but it can be applied to other vehicles such as trains and airplanes. It can also be applied to applications other than vehicles. It can also be applied to display devices such as projectors used indoors or outdoors. In FIG. 6, the anti-reflection film 10 is provided at three locations on the inner wall surface 3A of the housing 3, but the number and positions of the anti-reflection films provided in the housing 3 are not limited to this form. In addition, two reflecting mirrors are provided inside the housing 3, but depending on the design of the optical system, there may be only one reflecting mirror. EXAMPLES
[0075] Prior to the examples, the evaluation methods of the laminates of the examples will be described.
[0076] (Evaluation method) <Reflectance> The reflectance was measured using an optical member having an anti-reflection film on a surface of polycarbonate resin measuring 150 mm×70 mm.
[0077] The reflectance of the optical member was measured at wavelengths of 500 nm to 600 nm at angles of incidence of 85 degrees and 45 degrees every 1 nm using an ultraviolet-visible-near infrared spectrophotometer (manufactured by JASCO Corporation, product name: V-770), and the average value was taken as the reflectance. The measurement was performed after background correction. At an incident angle of 85 degrees, an average reflectance of less than 0.15% was rated as A, 0.15% or more but less than 0.2% was rated as B, and 0.2% or more was rated as C. At an incident angle of 45 degrees, an average reflectance of less than 0.015% was rated as A, 0.015% or more but less than 0.02% was rated as B, and 0.02% or more was rated as C.
[0078] <Strength of anti-reflective coating> A tape test was conducted to evaluate the adhesion of the anti-reflective coating. The test tape used was an adhesive tape specified in JIS Z 1522. The surface to which the tape was attached was used as the test surface, and the removed tape was observed under a microscope to evaluate the area of irregular fibers adhering to the adhesive surface. Specifically, the evaluation area was a rectangle measuring 2.0 mm wide x 1.5 mm long, and the total surface area ratio of irregular fibers present within this area was observed at five points on each sample, and the average value of the total surface area ratio of the irregular fibers was calculated. A total surface area ratio of irregular fibers less than 0.2% was rated A, and a total surface area ratio of 0.2% or more was rated B.
[0079] <Porosity of anti-reflective coating> The porosity of the anti-reflection film was measured using an optical member having an anti-reflection film provided on a surface of polycarbonate resin measuring 150 mm×70 mm.
[0080] The cross section of the anti-reflection film of the optical member was cut out using an ion milling device (Hitachi High-Technologies Corporation, product name: IM4000plus). The cross section of the sample was observed with a scanning electron microscope (SEM), and an image was obtained in which the area cut by ion milling was shown in black. The observation width in the X direction of this image was 15.8 mm, and 61A at the top of the cut cross section of the anti-reflection film was taken as the film thickness of the anti-reflection film, and the cross-sectional area of the anti-reflection film. The proportion of the black area in this cross-sectional area was subtracted from 100% to obtain the porosity.
[0081] <Distribution of the second component of the anti-reflection coating> The distribution of the second component (a layer consisting of silica particles and silica binder) in the Z direction (film thickness direction) of the antireflection film was performed using an optical component having an antireflection film provided on a surface of polycarbonate resin measuring 150 mm x 70 mm.
[0082] (Manufacture of laminates) Example 1 <Production of Paint A> First, we prepared a non-circular fiber A-1 (manufactured by Teijin Frontier Co., Ltd., product name: Octa) with a cross-sectional shape as shown in Figure 2(b). The non-circular fiber A-1 is made of polyester, has a thickness T of 25 μm, a core diameter of 12.5 μm, eight convex portions, a convex portion length CL of 6.25 μm, and a thickness CT of 3 μm.
[0083] Next, the irregular fiber A-1 was cut into lengths of 1 mm using a cutter, i.e., the aspect ratio, which is the ratio of the length to the thickness of the irregular fiber A-1, was 40. After cutting, the irregular fiber A-1 was dyed with a black dye.
[0084] The irregular fiber A-1 and acrylic resin were mixed in a beaker with a thinner, which is an organic solvent, so that the amount of the cut irregular fiber A-1 was 50 parts by mass relative to 100 parts by mass of the paint solid content. In order to adjust the color, a matte material or a colorant such as carbon black may be added separately. A stirrer was used for mixing, and the mixture was stirred at room temperature (23°C) at a speed of 200 rpm for 60 minutes to obtain paint A of Example 1.
[0085] <Production of Paint B> The IPA dispersion of chain particles in which solid silica particles are connected was evaporated to replace the 2-propanol solvent with 1-propoxy-2-propanol (Sigma), to prepare a 1-propoxy-2-propanol dispersion of chain particles (solid concentration 17wt%). For the IPA dispersion of chain particles, IPA-ST-UP (registered trademark) with a solid concentration of 15wt% manufactured by Nissan Chemical Industries, Ltd. was used. The solvent ratio was 2-propanol:1-propoxy-2-propanol=7.5:92.5.
[0086] 18.5 g of tetraethoxysilane and 16.0 g of 0.1 wt% phosphinic acid (10 equivalents to TEOS) as catalytic water were added, and mixed and stirred for 60 minutes in a 20°C water bath to prepare binder solution 1. Tetraethoxysilane is also called TEOS or ethyl silicate, and is manufactured by Tokyo Chemical Industry Co., Ltd.
[0087] 32.8g of binder solution 1, in which the components necessary to form a binder are equivalent to 0.5wt% in oxide conversion, was added to 251.3g of 1-propoxy-2-propanol dispersion of chain particles. Then, 174.5g of 1-propoxy-2-propanol and 546.5g of ethyl lactate were added to make the solid concentration of the chain particles 4.3wt% in oxide conversion, and the mixture was stirred for 60 minutes. Dispersion 1, which is paint B, was obtained with a weight ratio of 1-propoxy-2-propanol:ethyl lactate (with ether or ester bond, carbon number 5) = 40:60.
[0088] <Manufacture of the first and second members> Next, paint A was applied onto a polycarbonate resin substrate having a size of 150 mm×70 mm using a spray gun (manufactured by Anest Iwata Corporation, product name: W-200).
[0089] Thereafter, the polycarbonate resin substrate coated with paint A was placed in a thermostatic drying furnace set to 100°C and dried for 120 minutes. Next, paint B was sprayed onto the surface of this substrate coated with paint A. In order to grasp the coating thickness and refractive index of paint B, a silicon substrate was also sprayed under the coating conditions of paint B (hereinafter, referred to as the monitor substrate for paint B). Thereafter, the polycarbonate resin substrate coated with paints A and B and the silicon substrate coated with paint B were placed in a thermostatic drying furnace set to 120°C and dried for 30 minutes to obtain the laminate of Example 1.
[0090] The film thickness and refractive index were measured using a spectroscopic ellipsometry (JA Woollam EC-400) for an optical element in which an anti-reflection film was formed on a silicon substrate. The film thickness of the silica particle film was 800 nm, and the refractive index was 1.24.
[0091] Next, reflectance was measured at an incidence angle of 85 degrees and an incidence angle of 45 degrees. The results were A in both cases. After that, the adhesion of the anti-reflection coating was evaluated. The result was A.
[0092] Finally, a cross section of the laminate was cut out using an ion milling device. The cross section of the sample was observed using an SEM, and the area cut by ion milling was shown in black, resulting in the image shown in Figure 7. The porosity of this sample was 75%.
[0093] In addition, the cross section was evaluated by EDS analysis (analysis by energy dispersive X-ray spectroscopy) using a field emission scanning electron microscope. Figure 8(a) shows a C Kα line map analysis image (8-bit image) of the cross section of the anti-reflective coating, and Figure 8(b) shows a Si Kα line map analysis image (8-bit image) of the cross section of the anti-reflective coating. Figure 8(c) shows the intensity of the C Kα line and Si Kα line in the film thickness direction and the intensity ratio Si Kα / C Kα. Since the substrate is polycarbonate, the C Kα line intensity is high up to a distance of 500 μm in the Z direction, while the Si Kα line intensity is zero. At the 500 μm mark, there is a sharp drop in the C Kα line intensity and an increase in the Si Kα line intensity. In other words, the position 500 μm in the Z direction is the interface between the anti-reflective coating and the substrate. The surface of the anti-reflective coating is at 1000 μm, where both the C Kα line intensity and the Si Kα line intensity become zero. As can be seen from the Z-direction profile of the intensity ratio Si Kα / C Kα, the intensity ratio Si Kα / C Kα exceeds 1 in the upper layer (900 μm or more) of the antireflective film, whereas the intensity ratio Si Kα / C Kα is less than 0.6 in the lower layer (750 μm or less) of the antireflective film. This indicates that the second component (a layer made of silica particles and silica binder) with a large porosity of 75% is unevenly distributed in the upper layer of the film.
[0094] From the above results, it is possible to achieve low reflectance at high angles of incidence with a film made of resin and irregular fibers with micrometer-sized voids. Furthermore, it is believed that low reflectance can be achieved even at low angles of incidence by laminating a material with a lower refractive index than the irregular fibers and resin on the surface of the film. It is also believed that laminating a low refractive index material on the surface increases the binding strength of the irregular fibers and strengthens the adhesion of the film.
[0095] Example 2 The laminate of Example 2 was produced under the same conditions as Example 1, except that the spray coating conditions for Paint B were changed so that the film thickness of Paint B on the monitor substrate was 200 nm and the refractive index was 1.24. When the reflectance of the optical member of Example 2 was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. The adhesion strength of the anti-reflection film was also evaluated as A.
[0096] Example 3 The laminate of Example 3 was prepared by changing the preparation conditions of paint A, and mixing the irregular fiber A-1 and acrylic resin with a thinner, which is an organic solvent, in a beaker so that the amount of cut irregular fiber A-1 was 43 parts by mass relative to 100 parts by mass of the paint solid content. The subsequent spray application and drying conditions of paint A were the same as those of Example 1. The preparation conditions of paint B were the same as those of Example 1, and the spray application conditions of paint B were changed so that the film thickness of paint B on the monitor substrate was 400 nm and the refractive index was 1.24. The other conditions were the same as those of Example 1. When the reflectance of the optical member of Example 3 was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. In addition, the adhesion strength evaluation of the anti-reflection film was also A.
[0097] Example 4 The laminate of Example 4 was prepared by changing the preparation conditions of the paint A, and mixing the irregular fiber A-1 and the acrylic resin with the thinner, which is an organic solvent, in a beaker so that the amount of the cut irregular fiber A-1 was 56 parts by mass relative to 100 parts by mass of the paint solid content. The other conditions were the same as those of Example 3. When the reflectance of the optical member of Example 4 was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. The adhesion strength of the anti-reflection film was also evaluated as A.
[0098] Example 5 The laminate of Example 5 was produced by changing the preparation conditions of the paint A, and mixing the irregular fiber A-1 and acrylic resin with a thinner, which is an organic solvent, in a beaker so that the amount of the cut irregular fiber A-1 was 60 parts by mass relative to 100 parts by mass of the paint solid content. The other conditions were the same as those of Example 3. When the reflectance of the optical member of Example 5 was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. The adhesion strength of the anti-reflection film was also evaluated as A.
[0099] Example 6 Example 6 differs from Example 1 in that the chain silica particles contained in the paint B for forming the second member 23 were changed to hollow silica particles. Paint B was prepared by the following method.
[0100] 50g of 1E2P was placed in a flask. Then, 200g of hollow silica sol (Suluria 1110, manufactured by JGC Catalysts and Chemicals Co., Ltd.) with a solid content concentration of hollow particles of 20.5% by mass and a solvent of isopropyl alcohol (hereinafter referred to as IPA) was added to the flask, and 136g of 1E2P was further added. This mixture was reduced in pressure to 60hPa, heated to 45°C, and concentrated. After continuing the concentration for 30 minutes, the weight of the liquid was 205g. 1E2P, 1-butoxy-2-propanol (hereinafter referred to as 1B2P), and 2-ethyl-1-butanol (hereinafter referred to as 2E1B) were added to the concentrated liquid so that the ratio of the addition amount was 1E2P:1B2P:2E1B=38:31:31 to prepare a diluted liquid. This diluted liquid was stirred for 30 minutes to obtain a paint in which hollow particles were dispersed. 5 g of the paint in which the hollow particles were dispersed was heated to 1000° C., and the solid content was measured, which was found to be 3.805% by mass.
[0101] The preparation conditions and spray coating conditions of Paint A were the same as those of Example 3. The spray coating of Paint B was adjusted so that the film thickness on the monitor substrate was 400 nm, and the coating was applied to the substrate on which Paint A had been formed under the same conditions. The refractive index of Paint B on the monitor substrate was 1.23. When the reflectance of the laminate of Example 6 was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. The adhesion strength of the anti-reflection coating was also evaluated as A.
[0102] (Examples 7 to 9) In Examples 7 to 9, the type of non-circular fiber was changed as shown in Table 1, and an anti-reflective coating material and a laminate were obtained in the same manner as in Example 3. When the reflectance of the laminate of each Example was measured, the result was A for both the incident angle of 85 degrees and the incident angle of 45 degrees. The adhesion strength of the anti-reflective film was also evaluated as A.
[0103] (Examples 10 and 11) In Examples 10-11, the spray coating conditions of the paint B in Example 1 were changed, and the film thickness of the paint B on the monitor substrate was changed as shown in Table 1. The other conditions were the same as those in Example 1. When the reflectance of the laminate of Example 10 was measured, the result at an incident angle of 85 degrees was A, but the result at an incident angle of 45 degrees was B. In addition, the adhesion of the anti-reflection film was evaluated as A. It is considered that the reflectance reduction at a low incident angle was insufficient because the low refractive index portion was thin. When the reflectance of the laminate of Example 11 was measured, the result at an incident angle of 85 degrees was B, and the result at an incident angle of 45 degrees was A. In addition, the adhesion of the anti-reflection film was evaluated as A. It is considered that if the amount of paint B applied is large, the surface shape of the irregular fiber and the void structure in the anti-reflection film are changed, and the reflectance cannot be sufficiently reduced at a high incident angle.
[0104] [Table 1]
[0105] The types of irregular fibers are as follows: (A-1) Hollow 8-fin fiber Cross-sectional shape: Fig. 2(b), Material: polyester, Thickness T: 25 μm, Core diameter: 12.5 μm, Convex parts: 8, Convex part length CL: 6.25 μm, Convex part thickness CT: 3 μm (A-2) Hollow 8-fin fiber Cross-sectional shape: Fig. 2(b), Material: polyester, Thickness T: 50 μm, Core diameter: 25 μm, Convex parts: 8, Convex part length CL: 12.5 μm, Convex part thickness CT: 6 μm (A-3) Y-shaped nylon fiber Cross-sectional shape: Figure 3(a), Material: rayon, Thickness T: 20 μm, Core diameter: 3 μm, Convex parts: 3, Convex part length CL: 9.9 μm, Convex part thickness CT: 2.5 μm (A-4) Crimped fiber Cross-sectional shape: Fig. 3(d)(e), Material: polyester, Thickness T: 10 μm, Core diameter: 5 μm, Convex parts: 4, Convex part length CL: 2.5 μm, Convex part thickness CT: 2 μm (A-5) Spherical nylon fiber Cross-sectional shape: perfect circle, material: nylon, thickness T: 10 μm, protrusions: none
[0106] Comparative Example 1 <Preparation of paint A> First, spherical fiber A-5 having a circular cross-sectional shape was prepared. The spherical fiber A-5 was made of nylon and had a thickness T of 10 μm. That is, the cross-sectional diameter was 10 μm. Next, the spherical fiber A-5 was dyed with a black dye and then cut to a length of 1 mm using a cutter. That is, the aspect ratio, which is the ratio of the length to the thickness of the spherical fiber A-5, was 100. The spherical fiber A-5 and acrylic resin were mixed in a beaker with a thinner, which is an organic solvent, so that the cut spherical fiber A-5 was 50 parts by mass per 100 parts by mass of the paint solids. In addition, a coloring agent such as a matte material or carbon black may be added separately to adjust the color. A stirrer was used for mixing, and the mixture was stirred at a speed of 200 rpm at room temperature (23 ° C.) for 60 minutes to obtain paint A of Comparative Example 1.
[0107] The substrate, the spray application conditions of the coating material A, and other conditions were the same as those of Example 3 to produce a laminate of Comparative Example 1.
[0108] When the reflectance of the laminate of Comparative Example 1 was measured, the results were B for both the incident angle of 85 degrees and the incident angle of 45 degrees. In addition, the adhesion of the antireflection film was evaluated as A.
[0109] (Comparative Examples 2 to 5) In Comparative Examples 2 to 5, coating of paint B was not performed. Furthermore, the ratio of parts by mass of paint A to 100 parts by mass of the paint solid content of non-circular fiber A-1 in each Comparative Example was changed as shown in Table 1, and paint A was applied in the same manner as in Example 3 to obtain a laminate. When the reflectance of the optical members in each Example was measured, the result was A at an incident angle of 85 degrees, but B at an incident angle of 45 degrees. Furthermore, the adhesion strength of the anti-reflection film was also evaluated as B.
[0110] As described above, the laminate of the present disclosure is formed by sequentially laminating a first member and a second member on a substrate, the first member having a fiber and a binder, and having a void. Furthermore, if the second member has a lower refractive index than the first member, it is possible to provide both the light confinement effect at a high incidence angle of over 80 degrees due to the void portion and the reflection function at low incidence due to the low refractive index portion, so that a laminate with a superior anti-reflection function compared to the conventional technology can be provided. In particular, it is possible to provide an optical member that can achieve a low reflectance even at a low incidence angle of 45 degrees or less.
[0111] The present disclosure is not limited to the above-described embodiments, and many modifications are possible within the technical concept of the present disclosure. Furthermore, the effects described in the embodiments are merely a list of the most preferable effects resulting from the present disclosure, and the effects of the present disclosure are not limited to those described in the embodiments.
[0112] Although the above disclosure mainly describes the uses of optical members, the uses of the laminate are not limited to optical uses. The laminate can be imparted with functions such as hydrophilicity, antifouling, antibacterial properties, water resistance, and weather resistance. It can be used not only for optical devices, but also for the housings and exteriors of various articles such as electronic devices, structures, and buildings.
[0113] The disclosure of this embodiment includes the following configurations and methods.
[0114] (Section 1) A laminate in which a first member and a second member are laminated in this order on a substrate, The first member has fibers and a binder that binds the fibers, and has voids. A laminate comprising:
[0115] (Section 2) Item 2. The laminate according to item 1, wherein the second member has a refractive index lower than that of the first member.
[0116] (Section 3) When the total thickness of the first member and the second member is T, 3. The laminate according to item 1 or 2, wherein the amount of voids in a region up to a thickness T / 2 on a side farther from the substrate is greater than the amount of voids in a region up to a thickness T / 2 on a side closer to the substrate.
[0117] (Section 4) 4. The laminate according to any one of items 1 to 3, wherein the second member has a gap.
[0118] (Section 5) 5. The laminate according to item 4, wherein a porosity indicating a ratio of voids in the first member and the second member is in the range of 50% to 90%.
[0119] (Section 6) At least a portion of the fibers protrude from a binder that holds the fibers together; 6. The laminate according to any one of items 1 to 5, wherein the voids in the first member are formed by being surrounded by the fibers.
[0120] (Section 7) 5. The laminate according to item 4, wherein the maximum equivalent circle diameter of the voids in the second member is smaller than the maximum equivalent circle diameter of the voids in the first member.
[0121] (Section 8) 8. The laminate according to any one of items 1 to 7, wherein the maximum equivalent circle diameter of the voids in the first member is in the range of 1 μm to 200 μm.
[0122] (Section 9) Item 8. The laminate according to item 4 or 7, wherein the maximum equivalent circle diameter of the voids in the second member is in the range of 5 nm to 100 nm.
[0123] (Section 10) the second member is transparent; 10. The laminate according to any one of items 1 to 9, wherein the fibers and the binder binding the fibers are black.
[0124] (Section 11) 11. The laminate according to any one of items 1 to 10, wherein the second member has a thickness in the range of 100 nm to 1200 nm.
[0125] (Section 12) 11. The laminate according to any one of items 1 to 10, wherein the second member has a thickness in the range of 200 nm to 800 nm.
[0126] (Section 13) Item 13. The laminate according to any one of items 1 to 12, wherein the second member includes inorganic particles and a binder that binds the inorganic particles.
[0127] (Section 14) the inorganic particles are silicon oxide particles, Item 14. The laminate according to item 13, wherein the binder that binds the inorganic particles is a silica binder.
[0128] (Section 15) Item 15. The laminate according to item 14, wherein the silicon oxide particles are chain particles.
[0129] (Section 16) Item 15. The laminate according to item 14, wherein the silicon oxide particles are hollow particles.
[0130] (Section 17) Item 17. The laminate according to any one of items 1 to 16, wherein the fiber is a non-circular fiber having a core and a plurality of protrusions extending from the core.
[0131] (Section 18) Item 18. The laminate according to item 17, wherein the content of the non-circular fiber in the first member is in the range of 33 parts by mass to 67 parts by mass.
[0132] (Section 19) Item 19. The laminate according to item 17 or 18, wherein the length of the non-circular fiber is in the range of 0.2 mm or more and 1.0 mm or less.
[0133] (Section 20) 20. The laminate according to any one of items 17 to 19, wherein the length of the protrusions is in the range of 5 μm to 20 μm.
[0134] (Section 21) 21. The laminate according to any one of items 17 to 20, wherein the thickness of a cross section of the non-circular fiber in a direction perpendicular to the length direction is in the range of 10 μm to 50 μm.
[0135] (Section 22) Item 22. The laminate according to item 21, wherein the aspect ratio of the non-circular fiber, which is the ratio of the length to the thickness, is in the range of 4 to 100.
[0136] (Section 23) 23. The laminate according to any one of items 17 to 22, wherein the number of the protrusions is 3 to 8.
[0137] (Section 24) 24. The laminate according to any one of items 1 to 23, wherein the thickness of the binder binding the fibers is in the range of 10 μm to 700 μm.
[0138] (Section 25) 24. The laminate according to any one of items 1 to 23, wherein the thickness of the binder binding the fibers is in the range of 20 μm to 500 μm.
[0139] (Section 26) 26. The laminate according to any one of items 1 to 25, wherein the binder that binds the fibers is at least one resin selected from the group consisting of acrylic resin, urethane resin, and epoxy resin.
[0140] (Section 27) 27. The laminate according to any one of items 1 to 26, wherein the substrate comprises at least one selected from the group consisting of aluminum, titanium, stainless steel, and a magnesium alloy.
[0141] (Section 28) 28. The laminate according to any one of items 1 to 27, wherein the substrate comprises at least one selected from the group consisting of a polycarbonate resin, an acrylic resin, an ABS resin, and a fluororesin.
[0142] (Section 29) Item 29. The laminate according to any one of items 1 to 28, further comprising a primer layer between the substrate and the first member.
[0143] (Section 30) A housing and an optical system having at least one lens disposed within the housing, a first member and a second member are laminated in this order on a surface of a support that supports the lens and / or an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids. An optical instrument characterized by:
[0144] (Section 31) A housing and an optical system having at least one lens disposed within the housing; an image sensor that receives light that has passed through the optical system, a first member and a second member are laminated in this order on a surface of a support that supports the lens and / or an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids. 1. An imaging device comprising:
[0145] (Section 32) A housing and an image generating unit that generates image light and is provided in the housing; a reflecting mirror provided in the housing for reflecting image light emitted from the image generating unit and projecting the image light onto a display unit, a first member and a second member are laminated in this order on an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids. A display device comprising:
[0146] (Section 33) An optical member having an anti-reflection film laminated on a substrate, The anti-reflection film is formed by sequentially laminating a first member and a second member, The first member has fibers and a binder that binds the fibers, and has voids. The second member has a lower refractive index than the first member. An optical member characterized by:
[0147] (Section 34) An antifouling material in which a first member and a second member are laminated in this order on a substrate, The first member has fibers and a binder that binds the fibers, and has voids. The second member is made of a fluororesin. An antifouling member characterized by: [Explanation of symbols]
[0148] 1 Base material 100 Laminate 2 Anti-reflection coating 21 Binder (first member) 22 Deformed fiber (first component) 23 Second Component 24 Gap (first member, second member) 300 Head-up display (display device) 600 Single-lens reflex digital camera (imaging device) 601 Lens barrel (optical equipment)
Claims
1. A laminate in which a first member and a second member are laminated in this order on a substrate, The first member has fibers and a binder that binds the fibers, and has voids. A laminate comprising:
2. The laminate according to claim 1 , wherein the second member has a refractive index lower than that of the first member.
3. When the total thickness of the first member and the second member is T, The laminate according to claim 1 , wherein the amount of voids in a region up to a thickness T / 2 on the side farther from the substrate is greater than the amount of voids in a region up to a thickness T / 2 on the side closer to the substrate.
4. The laminate according to claim 1 , wherein the second member has a gap therein.
5. The laminate according to claim 4 , wherein a porosity indicating a ratio of voids in the first member and the second member is in the range of 50% or more and 90% or less.
6. At least a portion of the fibers protrude from a binder that holds the fibers together; The laminate according to claim 1 , wherein the voids in the first member are formed by being surrounded by the fibers.
7. 4. The laminate according to claim 3, wherein a maximum equivalent circular diameter of the voids in the second member is smaller than a maximum equivalent circular diameter of the voids in the first member.
8. 2. The laminate according to claim 1, wherein the maximum equivalent circle diameter of the voids in the first member is in the range of 1 μm to 200 μm.
9. The laminate according to claim 4 , wherein the maximum equivalent circle diameter of the voids in the second member is in the range of 5 nm to 100 nm.
10. the second member is transparent; 2. The laminate of claim 1, wherein the fibers and the binder binding the fibers together are black in color.
11. The laminate according to claim 1 , wherein the second member has a thickness in the range of 100 nm to 1200 nm.
12. The laminate according to claim 1 , wherein the second member has a thickness in the range of 200 nm to 800 nm.
13. The laminate according to claim 1 , wherein the second component contains inorganic particles and a binder that binds the inorganic particles together.
14. the inorganic particles are silicon oxide particles, 14. The laminate according to claim 13, wherein the binder that binds the inorganic particles is a silica binder.
15. The laminate according to claim 14 , wherein the silicon oxide particles are chain-like particles.
16. The laminate according to claim 14 , wherein the silicon oxide particles are hollow particles.
17. 2. The laminate according to claim 1, wherein the fibers are non-circular fibers having a core portion and a plurality of protrusions extending from the core portion.
18. The laminate according to claim 17 , wherein the content of the non-circular fiber in the first member is in the range of 33 parts by mass or more and 67 parts by mass or less.
19. The laminate according to claim 17, wherein the length of the irregularly shaped fibers is in the range of 0.2 mm or more and 1.0 mm or less.
20. 18. The laminate according to claim 17, wherein the length of the protrusions is in the range of 5 μm to 20 μm.
21. The laminate according to claim 17, wherein the cross-sectional thickness of the non-circular fiber in a direction perpendicular to the longitudinal direction is in the range of 10 μm to 50 μm.
22. 22. The laminate of claim 21, wherein the aspect ratio of the non-circular fiber, which is the ratio of the length to the thickness, is in the range of 4 or more and 100 or less.
23. The laminate according to claim 17, wherein the number of the protrusions is 3 or more and 8 or less.
24. 2. The laminate according to claim 1, wherein the thickness of the binder that binds the fibers is in the range of 10 μm to 700 μm.
25. 2. The laminate according to claim 1, wherein the thickness of the binder that binds the fibers is in the range of 20 μm to 500 μm.
26. 2. The laminate according to claim 1, wherein the binder that binds the fibers is at least one resin selected from the group consisting of an acrylic resin, a urethane resin, and an epoxy resin.
27. 2. The laminate according to claim 1, wherein the substrate comprises at least one selected from the group consisting of aluminum, titanium, stainless steel, and a magnesium alloy.
28. 2. The laminate according to claim 1, wherein the substrate comprises at least one selected from the group consisting of polycarbonate resin, acrylic resin, ABS resin, and fluororesin.
29. The laminate according to claim 1 , further comprising a primer layer between the substrate and the first member.
30. A housing and an optical system having at least one lens provided in the housing, a first member and a second member are laminated in this order on a surface of a support body that supports the lens and / or on an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids. An optical instrument characterized by:
31. A housing and an optical system having at least one lens disposed within the housing; an image sensor that receives light that has passed through the optical system, a first member and a second member are laminated in this order on a surface of a support that supports the lens and / or an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids.
1. An imaging device comprising:
32. A housing and an image generating unit that generates image light and is provided in the housing; a reflecting mirror provided in the housing for reflecting image light emitted from the image generating unit and projecting the image light onto a display unit, a first member and a second member are laminated in this order on an inner wall surface of the housing, The first member has fibers and a binder that binds the fibers, and has voids. A display device comprising:
33. An optical member having an anti-reflection film laminated on a substrate, The anti-reflection film is formed by sequentially laminating a first member and a second member, The first member has fibers and a binder that binds the fibers, and has voids. The second member has a lower refractive index than the first member. An optical member characterized by:
34. An antifouling material including a substrate, a first member, and a second member laminated in this order on the substrate, The first member has fibers and a binder that binds the fibers, and has voids. The second member is made of a fluororesin. An antifouling member characterized by:
Citation Information
Patent Citations
Optical system component
JP2011064737A
Anti-reflective coating material, optical member with Anti-reflective film, optical device, and image capturing device
JP2020008843A